Analysis of Landslides Susceptibility of the Erzincan-Sivas Road and Its Surrounding Region by the AHP Method based on Geographic Information Systems (GIS) - Betül Güneş; Ali Ümran Kömüşcü (Doğal Afetler ve Çevre Dergisi)
Landslides cause the highest human loss and economic damages following the earthquakes in Türkiye. This study aimed to identify areas that are susceptible to landslides in the Erzincan-Sivas highway and its surrounding region which frequently suffer from landslides based on the Analytic Hierarchy Process (AHP) Method using Geographic Information System (GIS) approach. A number of factors including slope, aspect, elevation, lithology, proximity to fault lines, proximity to rivers, proximity to main roads, precipitation, and vegetation density based on NDVI were considered in assessing the susceptibility of the region to landslides. The findings of the analysis indicate that a nearly 6,39 ha area along the Erzincan-Sivas highway has an extremely high susceptibility to landslides while 120 ha has a high susceptibility to landslides. Furthermore, the susceptibility to landslides is highest along and in the vicinity of the Erzincan-Sivas highway and decreases as it becomes distant from the Erzincan-Sivas highway. The study emphasizes the importance of early warning systems to increase resilience against landslides and proposes setting up an early warning system at the landslide-prone locations in the area.